THE CHILDREN'S ABILITY TO PRONOUNCE CAPITAL LETTERS IN WORDS AT THE AGE OF 2-3 YEARS IN KAMPUNG LALANG MEDAN - Lestin Marpaung; Debora Natio Silitonga; Devi Sulastri Saruksuk; Resperdiana Purba; Bambang Nur Alamsyah Lubis (ELT (English Language Teaching Prima Journal), 2022)
This research investigated the ability of children to pronounce the capital letter in words at 2-3 years at Kampung Lalang. Toddlers at the age of 2 years and up to 3 years would usually be able to say 50 words or more although some letters will still be difficult for them to pronounce. Vocabulary may grow rapidly but pronunciation may not keep up. There would be pronunciations that were difficult for them to pronounce even though they know what they were referring to. Only a few words and letters that they were able to pronounce and pronounce. The research aimed to find out the ability of children to pronounce the capital letter in words at 2-3 years at Kampung Lalang. The research was conducted in the house of parents that have the regional Kampung Lalang. This research was conducted by using Qualitative Descriptive methods. The instruments for collecting data were observation, interview, and oral-written documentation. The data analysis was the result of research in the house of parents that have the regional Kampung Lalang. After analyzing the folklore, the researcher found some capital letters that able to produced by the children and their ability to pronounce the capital letter in words. The letters were able to be pronounced by the children are A, B, C, D, E, G, H, I, J, K, L, M, N, O, P, Q, T, U, V, W, X, Y, Z. And the letters that were not able to be pronounced by the children are R and S. Keywords: Capital letter, Pronounce, The ability, Children.